Translations by Jack Kahane. - PEARSON, NEIL (Obelisk: A History of Jack Kahane & the Obelisk Press, 2007)
A list of translations by Jack Kahane which include "Princess of the Night," by Jospeh Kessel, "The Virgin Man," by Marcel Prevost, and "Restless Sands," by Marcel Prévost is presented.